Synthesis, characterization, and biological evaluation of novel Polyvinylpyrrolidone nanofibers containing Cassia angustifolia Vahl methanolic extract - Husen, Chou-Yi; Abdul-Reda Hussein, Uday; Mohammed, Amjed Qasim; Ramzy Muhammad, Eman; Al-Majdi, Kadhum; Radi, Usama Kadem; Ami, Ahmed Ali; Kareem, Anaheed Hussein; Ahmad, Irfan; Al-Shuwaili, Saeb Jasim; Huseen Redhee, Ahmed (Frontiers in Materials, 2024)
This study involved the preparation of the Saudi Arabia Cassia angustifolia vahl methanolic extract and the production of polyvinylpyrrolidone (PVP) nanofibers that contained the Saudi Arabia Cassia angustifolia vahl methanolic extract. The reason for using polyvinylpyrrolidone is its bioactivity and its physical and chemical properties. The structure and characterization of the newly synthesized nanofiber were confirmed using Fourier-transform infrared (FTIR) spectrum, Elemental analysis, scanning electron microscopy (SEM) image, N2 adsorption-desorption curve, curve, hydrophilicity, compressive strength, and flexural strength. The biological activity, including anticancer properties against skin cancer cells, bone cancer cells, and antibacterial activity against gram-positive and gram-negative strains, was assessed. The average diameter and the specific surface area of the synthesized polyvinylpyrrolidone nanofibers containing Saudi Arabia Cassia angustifolia vahl methanolic extract were 87 nm and 1108 m 2 /g, respectively. High hydrophilicity compared to polyvinylpyrrolidone (contact angle of synthetic nanofibers was 21 ° and for polyvinylpyrrolidone was 52 °), high compressive strength compared to polyvinylpyrrolidone (61.23 N/mm 2 and 34.52 N/mm 2 , respectively), high flexural strength compared to polyvinylpyrrolidone (16.1 N/mm 2 and 11.4 N/mm 2 , respectively) were other characteristics of synthesized polyvinylpyrrolidone nanofibers containing Saudi Arabia Cassia angustifolia vahl methanolic extract. In the biological activities of the synthesized nanofiber, unique properties were observed. In the anticancer activity, the IC50 value against skin cancer cells, and bone cancer cells were observed as 19.59 μg/mL, and 29.57 μg/mL, respectively. In the antimicrobial activity, the MIC value between 4-128 mg/mL was observed. The biological activities of synthesized polyvinylpyrrolidone nanofibers containing Saudi Arabia Cassia angustifolia vahl methanolic extract were higher than the Saudi Arabia Cassia angustifolia vahl methanolic extract. The biological properties can be enhanced by various factors, including the high specific surface area of the synthesized nanofiber.